Tractable computation in outage performance analysis of relay selection NOMA - Minh-Sang Van Nguyen; Dinh-Thuan Do (Universitas Ahmad Dahlan, 2020)
In recent years, using full-duplex (FD) transmission model provides enhanced bandwidth efficiency and improved performance for non-orthogonal multiple access (NOMA) system. However, lack of papers have investigated FD relay together with relay selection issue to improve performance of NOMA system. The problems in power allocation for two NOMA users satisfying fairness as well as relay selection strategy are studied in this paper. By considering the outage performance of proposed scheme with its vital result, general NOMA wireless networks can be developed for future networks due to its improved performance. Simulation results show that the relaying selection scheme can achieve a significant performance improvement by increasing required quantity of relay.